Acknowledgments, Livestock and Meat Industry Council Inc, Biological Variability (Kansas Agricultural Experiment Station Research Reports, 2017)
Listed below are individuals, organizations, and firms that have contributed to the beef research program through financial support, product donations, or services. We appreciate your help!
Keywords: beef cattle